2019
DOI: 10.1111/gcb.14665
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomy, together with ontogeny and growing conditions, drives needleleaf species' sensitivity to climate in boreal North America

Abstract: Currently, there is no consensus regarding the way that changes in climate will affect boreal forest growth, where warming is occurring faster than in other biomes. Some studies suggest negative effects due to drought‐induced stresses, while others provide evidence of increased growth rates due to a longer growing season. Studies focusing on the effects of environmental conditions on growth–climate relationships are usually limited to small sampling areas that do not encompass the full range of environmental c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 89 publications
(160 reference statements)
6
41
0
Order By: Relevance
“…Our results highlight that warming‐induced stomatal closure can occur in the absence of water limitation. Similarly, warming induced stomatal closure in congeneric, mature Norway spruce growing in its natural habitat (Lamba et al, 2018), suggesting that reductions in g s may contribute to the observed reduction in carbon gain and growth in black spruce across North America (Marchand et al, 2019), an effect likely exacerbated by soil water limitations (Girardin, Bouriaud, et al, 2016; Girardin et al, 2014; Girardin, Hogg, et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our results highlight that warming‐induced stomatal closure can occur in the absence of water limitation. Similarly, warming induced stomatal closure in congeneric, mature Norway spruce growing in its natural habitat (Lamba et al, 2018), suggesting that reductions in g s may contribute to the observed reduction in carbon gain and growth in black spruce across North America (Marchand et al, 2019), an effect likely exacerbated by soil water limitations (Girardin, Bouriaud, et al, 2016; Girardin et al, 2014; Girardin, Hogg, et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…We observed this effect in spruce, where declines in g s due to both warming and elevated CO 2 resulted in comparable carbon gain between seedlings grown under current (AC0T) and future climate conditions (EC8T), even when measured at their respective growth CO 2 (Figure 2b). While it is generally assumed that boreal forests are temperature limited (Huang et al, 2019), and might thus benefit from future climate warming and CO 2 fertilization (Stinziano & Way, 2014), these responses have not been observed in black spruce (Girardin, Bouriaud, et al, 2016; Marchand et al, 2019). Our results imply that stomatal responses (among other factors, such as nutrient and water availability) could dictate the long‐term trajectory of boreal forest productivity in future climates.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…where R is the tree radius and t is the year of tree-ring formation. Subsequently, BAIs was detrended using generalized additive mixed models (GAMMs) to remove the age-and size-related trends [43,44]. BAI values were log-transformed to improve the normality of their distributions.…”
Section: Long-term Growth Trendsmentioning
confidence: 99%